2019
DOI: 10.1186/s40677-019-0137-5
|View full text |Cite
|
Sign up to set email alerts
|

The performance of using an autoencoder for prediction and susceptibility assessment of landslides: A case study on landslides triggered by the 2018 Hokkaido Eastern Iburi earthquake in Japan

Abstract: Background: Thousands of landslides were triggered by the Hokkaido Eastern Iburi earthquake on 6 September 2018 in Iburi regions of Hokkaido, Northern Japan. Most of the landslides (5627 points) occurred intensively between the epicenter and the station that recorded the highest peak ground acceleration. Hundreds of aftershocks followed the major shocks. Moreover, in Iburi region, there is a high possibility of earthquakes occurring in the future. Effective prediction and susceptibility assessment methods are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…A certain number of sample data pieces of nonlandslide points need to be selected from the study area using random sampling methods to construct a binary classification model. Studies have shown that, in susceptibility assessment, the nonevent (nonlandslide points) sample size can be 2-10 times greater than the events (landslide points) (King and Zeng, 2001;Nam and Wang, 2019). After six experiments (the ratios of landslide and nonlandslide points were 1:5; 1:6; 1:7; 1:8; 1:9, and 1:10, respectively), the final ratio of landslide to nonlandslide was determined as 1:10; that is, 2,340 nonlandslide samples were selected.…”
Section: Data Preprocessingmentioning
confidence: 99%
“…A certain number of sample data pieces of nonlandslide points need to be selected from the study area using random sampling methods to construct a binary classification model. Studies have shown that, in susceptibility assessment, the nonevent (nonlandslide points) sample size can be 2-10 times greater than the events (landslide points) (King and Zeng, 2001;Nam and Wang, 2019). After six experiments (the ratios of landslide and nonlandslide points were 1:5; 1:6; 1:7; 1:8; 1:9, and 1:10, respectively), the final ratio of landslide to nonlandslide was determined as 1:10; that is, 2,340 nonlandslide samples were selected.…”
Section: Data Preprocessingmentioning
confidence: 99%
“…The autoencoder is trained to reconstruct the input of the landslide-influencing factors onto the output layer for feature extraction and dimensionality reduction. The methods prevent the simple copying of the data and the network [121]. Maher et al [146] used an autoencoder as an optimized factor to learn features from a dataset in an unsupervised manner [58].…”
Section: Autoencodermentioning
confidence: 99%
“…The autoencoder is trained to reconstruct the input of the landslide-influencing factors onto the output layer for feature extraction and dimensionality reduction. The methods prevent the simple copying of the data and the network [135].…”
Section: Autoencodermentioning
confidence: 99%